Effects of repetitive transcranial magnetic stimulation combined with sensory cueing on unilateral neglect in subacute patients with right hemispheric stroke: a randomized controlled study. (September 2017) - Yang, Nicole YH; Fong, Kenneth NK; Li-Tsang, Cecilia WP; Zhou, D
Objective: To compare the effects of rTMS combined with sensory cueing, rTMS alone, and conventional rehabilitation on unilateral neglect, hemiplegic arm functions and performance of activities of daily living. Design: A single-blinded randomized controlled trial. Setting: A convalescent hospital. Subjects: Sixty inpatients with left unilateral neglect after stroke. Interventions: Patients were randomly assigned to three groups: rTMS combined with sensory cueing, rTMS, and conventional rehabilitation alone. rTMS at 1 Hz was applied over P5 of the contralesional hemisphere while vibration cueing was emitted using a wristwatch device on the hemiplegic arm, five days per week for two weeks. The first two groups received the same dosage of conventional rehabilitation on top of their experimental interventions. Blinded assessments were administered at baseline, 2 weeks postintervention, and 6 weeks follow-up. Main measures: Neglect and arm motor performance. Results: Both rTMS combined with sensory cueing (99.6±33.0) and rTMS alone (88.2±28.7) significantly reduced unilateral neglect than conventional rehabilitation (72.7±33.1) when measured using the conventional subtests of the Behavioural Inattention Test, but the combination was better than rTMS alone. Hemiplegic arm functions and activities of daily living improved in all patients across the three groups but no significant differences were found between the groups. Conclusion: The combination of inhibitory P5-rTMS with sensory cueing was better than either rTMS or conventional rehabilitation alone in producing a stronger and long-lasting improvement in unilateral neglect, but the improvement was not associated with improved arm function or independence in activities of daily living.